Problem Behavior in Autism Spectrum Disorder: Considering Core Symptom Severity and Accompanying Sleep Disturbance - Lindor, Ebony; Sivaratnam, Carmel; May, Tamara; Stefanac, Nicole; Howells, Katherine; Rinehart, Nicole (Frontiers in Psychiatry, 2019)
In addition to the core symptoms that define Autism Spectrum Disorder (ASD), many individuals experience broader problem behaviour at a level significant enough for families to seek further clinical assessment and intervention. We define ‘problem behaviour’ as any significant emotional or behavioural issue captured by the Child Behavior Checklist (CBCL) including anxiety, depression, withdrawal, somatic complaints, problems with socialisation, thought or attention, rule-breaking, and aggression. While greater ASD symptom severity and accompanying sleep disturbance have each been linked with more severe problem behaviour, there is little understanding about how these two key factors interact; that is, it is unclear whether the severity and type of sleep disturbance an individual experiences differentially influences the relationship between ASD symptom severity and problem behaviour. The aim of the current study was, thus, to explore whether the link between greater ASD symptom severity and clinically elevated problem behaviour is moderated by the presence/degree of accompanying sleep disturbance. Forty males with ASD, aged 5-to-12, participated in the study. The Social Responsiveness Scale, CBCL and Child Sleep Habits Questionnaire were administered to obtain information about ASD symptom severity, problem behaviour and sleep habits respectively. Results indicated that the relationship between ASD symptom severity and problem behaviour differed among individuals with ASD depending on the degree of sleep disturbance they experienced. Specifically, there was a significant positive relationship between ASD symptom severity and problem behaviour for individuals with no sleep disturbance or milder sleep disturbance (i.e., in these cases individuals with severe ASD symptoms experienced clinically elevated problem behaviour while those with milder ASD symptoms experienced milder problem behaviour). In contrast, there was no significant relationship between ASD symptom severity and problem behaviour for individuals with moderate-to-severe sleep disturbance; rather, clinically significant problem behaviour was apparent across all individuals irrespective of ASD symptom severity. Follow-up analyses indicated that disturbances in sleep duration, disordered breathing and daytime sleepiness were related to clinically elevated problem behaviour even among those with milder ASD symptoms. These findings emphasise the importance of routinely assessing for accompanying sleep disturbance in this population regardless of whether individuals present with mild, moderate or severe ASD.